Kitten's first full moon. - Henkes, Kevin ([New York] : Greenwillow Books, 2004)
When Kitten mistakes the full moon for a bowl of milk, she ends up tired, wet, and hungry trying to reach it
Caldecott 2005 Medal Winner
K-3
Keywords: Cats--Fiction; Animals--Infancy--Fiction.; Moon--Fiction.